Studies on the activity of the standardized extracts of Piper betle L. and Piper nigrum L. on Mycobacterium tuberculosis : cellular and metabolomics approaches - Patilaya, Popi (2012)
The rising of drug-resistance tuberculosis (TB) cases has prompted an urgent need for a new anti-TB drug preferably from local medicinal plants. However, in the last decade not much attention has been given to the microbiology and metabolomics aspects of these plants regarding to their anti-TB activity. This study was carried out to test the antimycobacterial activity of standardized extracts and fractions of Piper betle and Piper nigrum. The extracts and fractions were prepared with maceration and liquid-liquid partition method, respectively. The activity was tested using tetrazolium microdilution assay. The effects of the active fraction on the growth of Mycobacterium tuberculosis was also studied under light and scanning electron microscopy observation. HPLC and FTIR spectroscopy in combination with PCA were used to profile the extract and fraction. Toxicity testing of the active extracts and fraction was performed using Brine Shrimp method. The results indicated that extracts of P. betle and P. nigrum exhibited antimycobacterial activity with MIC values ranging from 100 μg/ml to 500 μg/ml while the MIC of the fractions was 25-100 μg/ml. Evaluation under light microscopy showed that the active fractions affected the growth of mycobacterial cells causing loss of acid-fastness and morphological changes. Under scanning electron microscopy the affected cells appeared wrinkled and empty due to release of cytoplasmic materials from ruptured cells. HPLC analysis showed that the extract and fraction of P. betle contain 0.065% and 0.010% eugenol, respectively. Meanwhile extract and fraction of P. nigrum contain 1.215% and 0.060% piperine,respectively. Principal component analysis (PCA) was able to differentiate the leaf ethanol/water (1:1) extract of P. betle, the leaf ethanol extract of P. nigrum, and its ethyl acetate fractions based on the FT-IR spectra. Toxicity test indicated that the active extract had low toxicity with LD50 >1000 μg/ml while the LD50 of the ethyl acetate fractions of P. betle and P. nigrum were 90.78 μg/ml and 137.90 μg/ml, respectively. This study indicated that both P. betle and P. nigrum have potential antimycobacterial activity.